The role of logistics management activities in improving the productive work environment: A survey study on a sample of employees in the General Company for Electrical Industries (Texas Journal of Multidisciplinary Studies, 2024)
Logistics management is one of today's tools to face economic challenges. It is a combination of the basic business and activities of the organization. The current research aims to identify the logistics systems and the extent of the organization's commitment to them to ensure the improvement of its production environment. The research hypotheses were developed to achieve its objectives and directions, and (45) questionnaire forms were distributed to the employees of the General Company for Electrical Industries. The research hypotheses were tested and the obtained data were analyzed by adopting a set of statistical methods, and the results were extracted according to the analysis by employing the data of the program (Spss.Ver.13). Based on the description of the research variables, their diagnosis and testing of its hypotheses, a set of results were reached, and in light of them, conclusions were formulated. The most prominent of these was that the results revealed that there is a weakness in some logistical activities, including inventory management, distribution management, material handling and packaging, and the lack of complete unification of work within the company, which creates a weakness in the impact on the productive work environment.